2021
DOI: 10.5713/ajas.20.0445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with different fermented feeds on performance, nutrient digestibility, and serum biochemical indexes of fattening lambs

Abstract: Objective: The effects of adding fermented feed to a pelleted total mixed ration (PTMR) on the growth performance of lambs remain unclear. The present study aimed to investigate the feed efficiency and productivity of lambs that were fed PTMR containing fermented soybean meal (FSM) or wheat bran (FWB).Methods: Sixty 90-d-old hybrid lambs were randomly allocated into 12 pens (5 lambs/pen) that were randomly assigned to 4 dietary treatments (3 pens/treatment) with PTMR (basal diet), 2% FSM, or <i>Lactobaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…In this study, the content of TVFA and propionate proportion also exerted the positive linkage with the increased abundance of microbes in the rumen of lambs fed PTMR diet. This was consistent with the findings of Zhang et al (2021) , who reported that fermentation products in the rumen were related to dietary composition and rumen microbes. The pelleting process denatures proteins, gelatinizes starch, and hydrolyzes some fiber components, all of which contribute to the proliferation of beneficial ruminal microbes ( Blanco et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the content of TVFA and propionate proportion also exerted the positive linkage with the increased abundance of microbes in the rumen of lambs fed PTMR diet. This was consistent with the findings of Zhang et al (2021) , who reported that fermentation products in the rumen were related to dietary composition and rumen microbes. The pelleting process denatures proteins, gelatinizes starch, and hydrolyzes some fiber components, all of which contribute to the proliferation of beneficial ruminal microbes ( Blanco et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, exploring workable strategies, improving the roughage efficiency, and establishing the stable feed supply system for promoting the development of the fattening lamb industry are important. Diet characteristics, such as ingredients, shape, smell, particle size, and processing methods, affect G/F and animal feed intake ( Bi et al, 2019 ; Ran et al, 2021 ; Zhang et al, 2021 ). The pelleted total mixed ration (PTMR) has been shown to enhance the G/F and growth performance of lambs ( Zhang et al, 2019 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid extraction from breast muscle samples was performed by the Folch et al method [ 17 ]. The extracted lipid was hydrolyzed in 2 mL KOH–methanol (C = 0.5 mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, probiotic fermentation technology has become a powerful tool to reduce anti-nutritional factors in feed, and improve nutritional quality and the bioavailability of nutrients [ 16 , 17 ]. Therefore, in this study, the mixed strains of Lactobacillus , Saccharomycetes , and Bacillus subtilis were used to ferment mulberry leaf powder to investigate the effects of fermented mulberry leaf powder on production performance, slaughter performance, and meat quality of broilers, so as to provide a theoretical basis for the application of fermented mulberry leaf in livestock production, especially in areas where mulberry leaves are widely planted.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the fermentation of silage could significantly reduce the contents of the crude fiber and antinutritional factors in mulberry leaves, minimize nutrient loss, and improve the palatability of mulberry leaves, which is the most commonly used processing method for livestock and poultry feed [ 15 , 16 ]. Microbial fermentation technology can transform the indigestible macromolecules in mulberry leaves into digestible small molecules, such as amino acids, small peptides, and organic acids, and can release their nutrients [ 17 ]. In our study, the results showed that, compared with maize silage, the crude protein (CP) and ether extract (EE) content of mulberry silage increased by 9.1% and 2.84%, respectively, and the neutral detergent fiber (NDF) content decreased by 7.08%, which was ideal for ruminant feed materials.…”
Section: Introductionmentioning
confidence: 99%